Math 304-504 Linear algebra Lecture 34: Matrix exponentials. Exponential function Exponential function: f (x) = exp x = e x , x ∈ R. We have that e x+y = e x · e y . x n x Definition 1. e = lim 1 + . n→∞ n 1 n ≈ 2.7182818. In particular, e = lim 1 + n→∞ n x2 xn Definition 2. e = 1 + x + + ··· + + ··· 2! n! x Definition 3. f (x) = e x is the unique solution of the initial value problem f ′ = f , f (0) = 1. Complex exponentials Definition. For any z ∈ C let z2 zn z e =1+z + + ··· + + ··· 2! n! Remark. A sequence of complex numbers z1 = x1 + iy1 , z2 = x2 + iy2 , . . . converges to z = x + iy if xn → x and yn → y as n → ∞. Theorem 1 If z = x + iy , x, y ∈ R, then e z = e x (cos y + i sin y ). In particular, e iφ = cos φ + i sin φ, φ ∈ R. Theorem 2 e z+w = e z · e w for all z, w ∈ C. Proposition e iφ = cos φ + i sin φ for all φ ∈ R. Proof: e iφ (iφ)n (iφ)2 + ··· + + ··· = 1 + iφ + 2! n! The sequence 1, i, i 2 , i 3 , . . . , i n , . . . is periodic: 1, i, −1, −i , 1, i, −1, −i , . . . | {z } | {z } It follows that φ2 φ4 φ2k e iφ = 1 − + − · · · + (−1)k + ··· 2! 4! (2k)! 2k+1 φ3 φ5 φ + i φ− + − · · · + (−1)k + ··· 3! 5! (2k + 1)! = cos φ + i sin φ. Matrix exponentials Definition. For any square matrix A let 1 1 exp A = e A = I + A + A2 + · · · + An + · · · 2! n! Matrix exponential is a limit of matrix polynomials. Remark. Let A(1) , A(2) , . . . be a sequence of n×n (n) matrices, A(n) = (aij ). The sequence converges to (n) an n×n matrix B = (bij ) if aij → bij as n → ∞, i.e., if each entry converges. Theorem The matrix exp A is well defined, i.e., the series converges. Properties of matrix exponentials Theorem 1 If AB = BA then e A e B = e B e A = e A+B . Corollary (a) e tA e sA = e sA e tA = e (t+s)A , t, s ∈ R. (b) (e A )−1 = e −A . Theorem 2 d tA e = Ae tA = e tA A. dt tn n t2 2 Indeed, e = I + tA + A + · · · + A + · · · , 2! n! and the series can be differentiated term by term. t n−1 d tn d tn n n A = = A An . dt n! dt n! (n − 1)! tA Lemma Let A be an n×n matrix and x ∈ Rn . Then the vector function v(t) = e tA x satisfies v′ = Av. d dv = e tA x = Ae tA x = A e tA x = Av. Proof: dt dt Theorem For any t0 ∈ R and x0 ∈ Rn the initial value problem dv = Av, v(t0 ) = x0 dt has a unique solution v(t) = e (t−t0 )A x0 . Indeed, v(t) = e (t−t0 )A x0 = e tA e −t0 A x0 = e tA x, where x = e −t0 A x0 is a constant vector. Problem. Solve a system of differential equations ( dx dt = 2x + 3y , dy dt = x + 4y subject to initial conditions x(0) = 2, y (0) = 1. Let v(t) = (x(t), y (t)). Then the system can be dv 2 3 rewritten as = Av, where A = . 1 4 dt The unique solution is v(t) = e tA x0 , where x0 = (2, 1). Example. A = diag(a1 , a2 , . . . , ak ). An = diag(a1n , a2n , . . . , akn ), n = 1, 2, 3, . . . 1 2 1 A + · · · + An + · · · 2! n! = diag(b1 , b2 , . . . , bk ), eA = I + A + where bi = 1 + ai + 1 2 1 3 ai + ai + · · · = e ai . 2! 3! Theorem If A = diag(a1 , a2 , . . . , ak ) then e A = diag(e a1 , e a2 , . . . , e ak ), e tA = diag(e a1 t , e a2 t , . . . , e ak t ). Let A be an n-by-n matrix and suppose there exists a basis v1 , . . . , vn for Rn consisting of eigenvectors of A. That is, Avk = λk vk , where λk ∈ R. Then A = UBU −1 , where B = diag(λ1 , λ2 , . . . , λn ) and U is a change-of-coordinates matrix whose columns are vectors v1 , v2 , . . . , vn . A2 = UBU −1 UBU −1 = UB 2 U −1 , A3 = A2 A = UB 2 U −1 UBU −1 = UB 3 U −1 . Likewise, An = UB n U −1 for any n ≥ 1. I + 2A − 3A2 = UIU −1 + 2UBU −1 − 3UB 2 U −1 = = U(I + 2B − 3B 2 )U −1 . =⇒ p(A) = Up(B)U −1 for any polynomial p(x). =⇒ e tA = Ue tB U −1 for all t ∈ R. Example. A = 2 3 . 1 4 The eigenvalues of A: λ1 = 1, λ2 = 5. Eigenvectors: v1 = (3, −1), v2 = (1, 1). Therefore A =UBU −1 , where 1 0 3 1 B= , U= . 0 5 −1 1 Then t 3 1 e e tA = Ue tB U −1 = −1 1 0 t 5t t 3e e 3e 1 1 −1 1 = = 4 −e t −e t e 5t 4 1 3 0 e 5t 3 1 −1 1 −1 + e 5t −3e t + 3e 5t . + e 5t e t + 3e 5t Problem. Solve a system of differential equations ( dx dt = 2x + 3y , dy dt = x + 4y subject to initial conditions x(0) = 2, y (0) = 1. The unique solution: x(t) 2 tA = e x0 , where A = y (t) 1 t 3e + e 5t −3e t 1 tA e =4 −e t + e 5t et ( x(t) = 43 e t + 54 e 5t , =⇒ y (t) = − 14 e t + 54 e 5t . 3 2 , x0 = . 4 1 + 3e 5t + 3e 5t 0 1 0 Example. A = 0 0 1, a Jordan block. 0 0 0 0 0 1 2 A = 0 0 0, A3 = O, An = O for n ≥ 3. 0 0 0 1 1 12 1 e A = I + A + A2 = 0 1 1, 2 0 0 1 1 t 21 t 2 2 t e tA = I + tA + A2 = 0 1 t . 2 0 0 1 1 1 Example. A = , another Jordan block. 0 1 1 2 1 3 1 n A2 = , A3 = , An = . 0 1 0 1 0 1 tn n t2 2 a(t) b(t) tA , e = I +tA+ A + · · · + A + · · · = 0 a(t) 2! n! where a(t) = 1 + t + 2 3 t2 2! + t3 3! + · · · = et, b(t) = t + 2 t2! + 3 t3! + · · · = te t . t t e te Thus e tA = . 0 et λ 1 Example. A = , a general Jordan block. 0 λ 0 1 We have that A = λI + B, where B = . 0 0 Since (λI )B = B(λI ), it follows that e A = e λI e B . Similarly, e tA = e tλI e tB . λt e 0 e tλI = = e λt I , 0 e λt 1 t . B 2 = O =⇒ e tB = I + tB = 0 1 λt λt e te Thus e tA = e tλI e tB = . 0 e λt Problem. Solve a system of differential equations ( dx dt = 2x + y , dy dt = 2y subject to initial conditions x(0) = y (0) = 1. The unique solution: x(t) 2 1 1 tA = e x0 , where A = , x0 = . y (t) 0 2 1 2t 2t 1 t e te e tA = = e 2t 0 1 0 e 2t ( x(t) = e 2t (1 + t), =⇒ y (t) = e 2t .